1992
DOI: 10.3354/meps083071
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of anoxia on Mytilus galloprovincialis

Abstract: In mussels Mytilus galloprovincialis Lmk. exposed to the air or kept in oxygen-free seawater, the frequency of micronuclei detected in gill tissues significantly rises as a function of time. It is suggested that the genotoxic agent may b e a product of anaerobic metabolism, and the genotoxicity of propionic and acetic acid are shown, although the possibility that other substances may b e involved in the phenomenon is not excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Comparable tissue differences, of spontaneous micronuclei frequencies, between gill cells and hemocytes, have also been reported in other studies, with different species of bivalves (Siu et al, 2004). For example in the mussel M. galloprovincialis from unpolluted Mediterranean areas, the baseline level of MN frequencies in the hemocytes of mussels varies between 1 and 3‰ (Brunetti et al, 1992a,b), knowing that it could vary with age, sex, season, temperature, oxygen, and other factors (Barsiene et al, 2003;Brunetti et al, 1988Brunetti et al, , 1992b.…”
Section: Micronucleus Frequencymentioning
confidence: 77%
See 1 more Smart Citation
“…Comparable tissue differences, of spontaneous micronuclei frequencies, between gill cells and hemocytes, have also been reported in other studies, with different species of bivalves (Siu et al, 2004). For example in the mussel M. galloprovincialis from unpolluted Mediterranean areas, the baseline level of MN frequencies in the hemocytes of mussels varies between 1 and 3‰ (Brunetti et al, 1992a,b), knowing that it could vary with age, sex, season, temperature, oxygen, and other factors (Barsiene et al, 2003;Brunetti et al, 1988Brunetti et al, , 1992b.…”
Section: Micronucleus Frequencymentioning
confidence: 77%
“…Other authors, such as Brunetti et al (1988Brunetti et al ( , 1992b, reported that physical factors, such as temperature, can change the micronuclei frequency of mussels. Moreover, Bolognesi and Cirillo (2014) added that it was shown that the temperature of water has a direct effect on the mitotic rate, and hence on the formation of micronuclei (MN).…”
Section: Micronucleus Frequencymentioning
confidence: 97%
“…Also such factors as intensive eutrophication and the lack of oxygen in Malkų Bay can play a role in genotoxic damage. It is known that anoxia has caused an increase in the frequency of micronuclei in molluscs (BRUNETTI et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increasing interest towards the use of micronuclei as an index of cytogenetic damage in fish and other marine organisms exposed to a variety of toxic and genotoxic pollutants under laboratory (Al-Sabti, 1986a,b;Al-Sabti, 1994;Al-Sabti et al, 1994;Al-Sabti, 1995b;Burgeot et al, 1995;Venier et al, 1997;Marlasca et al, 1998) and field conditions (Al-Sabti & Hardig, 1990;Al-Sabti, 1992a,b;Burgeot et al, 1996a;Rao et al, 1997). Micronuclei detection assay has been employed in genotoxicity studies carried out in invertebrates (Brunetti et al, 1992;Burgeot et al, 1995Burgeot et al, , 1996bVenier et al, 1997), fish (Al-Sabti et al, 1994;Al-Sabti, 1995b;Rao et al, 1997;Marlasca et al, 1998) and humans (Fenech et al, 1994;Vral et al, 1994). Currently, MN detection represents a widely used parameter, easily performed, which also allows molecular approaches in studying the effects of many clastogenic or aneugenic agents (Venier et al, 1997).…”
Section: 7)mentioning
confidence: 99%